Pedagogy Design in Responsible Tourism Vis-À-Vis Challenges of Sustainable Development- A Qualitative Study on Reports and Cases of Research and Advocacy Organisations - Chandran, Anu; M, Kanthan (Journal of Tourism Management Research, 2015)
Responsible tourism has become a buzzword in tourism industry in the 21st century and refers to conscious travel to natural areas with the core objective of preserving the environment resources, while both the promoters of tourism and the local communities are being utmost sensitive to the ecological and cultural aspects of the destinations. The quality of the environment is basic for tourism development. The environment has to be examined from various dimensions, mainly in terms of its physical characteristics. It is saddening that tourism activities are negatively impacting the environmental resources. The deterioration of a host area will defeat the purposes of tourism development. The concept of responsible tourism has indeed revolutionized the dynamics of tourism across the globe. The core objective of responsible tourism, which has ushered in a paradigm shift in sustainable development approaches world over, is the motive to conserve the eco-cultural resources and increase the value of local culture and tradition. In consonance with the changing patterns, practices, and propositions of responsible tourism, the pedagogy has not been quite progressive. In this backdrop, the present article carries out a qualitative study on the case studies and reports of select research and advocacy organizations in south India which are striving to enhance the educational contents and structure as regards responsible tourism with a view to achieve sustainable development of tourism destinations. Moreover, the recommendations, dossiers, and study results published by the premier tourism consultancies are evaluated and the concrete points which surfaced so as to be included in the RT pedagogy have been confirmed by interviews with the experts.